(untitled) (Филолошке студије, 2019)
: It is necessary to start the speculations on history and its repetition in the novels of Croatian literature with Senoa and the concept of history developed in his historical novels. For Senoa, history is magistra vitae, the teacher of life, which expresses his attitude that, based on the acquired experiences, you can avoid mistakes and find better solutions. However, the genre of historical novel in Croatian literature has been constantly changing, as well as the concept of history within it and the affirmative attitude towards the past has been replaced by the vision of history as the time of suffering, evil, madness and death. Such a negative attitude towards history will be depicted in this paper through the examples of three novels: Practicing life (1985) by Nedjeljko Fabrio, The Confessions of Charactereless Man (1990) by Ivo Bresan and The Bridge on the Drina (1945) by Ivo Andric. All three novels evidently show a drastic decline from Senoa’s concept of history. The mentioned authors in their novels openly criticize Senoa’s attitude to history as the teacher of life, as they do not think something can be learnt from history. An affirmative attitude towards history has been replaced by a vision of history as a source of evil, agony and suffering. The main idea of historical circulus, i.e. recognition of the present through the past and vice versa and their permanent turns, has marked all three mentioned novels.